2020
DOI: 10.2196/22478
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Strategies to Tackle Skin Neglected Tropical Diseases With Recommendations From Innovative Experiences: Systematic Review

Abstract: Background Neglected tropical diseases (NTDs) represent a diverse group of 20 communicable diseases that occur in tropical and subtropical areas in 149 countries, affecting over 1 billion people and costing developing economies billions of dollars every year. Within these diseases, those that present lesions on the skin surface are classified as skin NTDs (sNTDs). Mobile health interventions are currently being used worldwide to manage skin diseases and can be a good strategy in the epidemiologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…Second, only three published papers examined NTDs (on lymphatic filariasis and scabies) in the Pacific, creating a dearth of qualitative evidence from which to guide implementation of effective NTD control programs in the Pacific region more specifically. Our analysis contributes to the growing body of NTD-related systematic, rapid and scoping reviews with a focus on, for example, social stigma [60]; treatment adherence [61,62]; community understandings of mass drug administration for specific NTDs [63]; the role of nurses, community health workers and community drug distributors in responses to NTDs [64] [65,66]; and innovation in responses to tackling NTDs [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Second, only three published papers examined NTDs (on lymphatic filariasis and scabies) in the Pacific, creating a dearth of qualitative evidence from which to guide implementation of effective NTD control programs in the Pacific region more specifically. Our analysis contributes to the growing body of NTD-related systematic, rapid and scoping reviews with a focus on, for example, social stigma [60]; treatment adherence [61,62]; community understandings of mass drug administration for specific NTDs [63]; the role of nurses, community health workers and community drug distributors in responses to NTDs [64] [65,66]; and innovation in responses to tackling NTDs [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of digital innovations by health teams as a facilitating instrument for the management and monitoring of patients' health is a relevant strategy for improving leprosy control actions [27]. The Hansenapp proved to be a promising technological tool to assist healthcare providers in caring for leprosy patients and monitoring contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the studies we reviewed employed mobile applications and AI in conjunction with TD, we acknowledge the potential synergy of combining these technologies. Recently, Carrion et al reviewed the utility of mobile applications in mitigating the burden of sNTDs and although they concluded that numerous barriers to widespread mobile health implementation remain, their review demonstrates that creative mobile technologies, some with a modicum of success, do exist and can help curb the morbidity associated with sNTDs [32]. Adding AI can further potentiate the power of TD.…”
Section: Teledermatology: Advantages and Promisesmentioning
confidence: 99%